2012
DOI: 10.5187/jast.2012.54.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carcass Traits on Auction Price in Hanwoo

Abstract: The aim of this study was to estimate the effect of sex, slaughtered season and year on carcass traits, and the contribution of carcass traits to auction and total prices. The data used in this study were the carcass grade of Hanwoo (4,231 heads) slaughtered from 2008 to 2010. Carcass traits were affected significantly (p<0.01) by sex, slaughtered season and year. The R-Square of auction prices, analyzed the contribution of causes using the squared semi-partial correlation, was 0.55. The contributions of aucti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…That result was different in this study. The research of Sun et al (2012) indicates that the marbling score effect was absolute high. The results of Sun et al (2012) are similar to the results of this study.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…That result was different in this study. The research of Sun et al (2012) indicates that the marbling score effect was absolute high. The results of Sun et al (2012) are similar to the results of this study.…”
Section: Resultsmentioning
confidence: 95%
“…The exact contribution analysis of factors towards the unit price enhances farmer income through decreases in production cost and improvement in the efficiency of breeding plans. Thus, estimation of the unit price and the effect of genetic parameters on carcass traits have been studied; examples include the contribution analysis of carcass traits towards the unit price of Hanwoo beef (Park et al , 2015; Sun et al , 2012), and the estimation of the effect of genetic parameters on carcass traits (Koo et al , 2011; Sun et al , 2010; Utama et al , 2017; Yoon et al , 2002). The contribution analysis of carcass traits towards unit price in Hanwoo beef is important because farmers can utilize the results to improve planning.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the tendency of the inverse relationship between meat quality and carcass yield, Hanwoo farmers need to make a decision for a proper balance between them for maximizing profit. According to a study on the price change of carcasses by grading determinants of meat quality and yield, the effect of marbling and the carcass weight on total price was estimated by 46.3%, and 52.4%, respectively, and the marbling particularly was evaluated to contribute on auction price with 93.5% [15]. In addition, it was reported that the marbling was the significant factor affecting both carcass price and auction price in determining grid price and prediction of carcass composition [13], which indicates the importance of the meat quality factor in determining Hanwoo price.…”
Section: Discussion On Identification Of Optimal Factors Based On Ecomentioning
confidence: 99%
“…In addition, meat color, which is one of the determinant factors for meat quality, is a dominant consumer preference because they generally prefer scarlet-colored beef [14]. Additionally, there are studies evaluating the genetic relationship between carcass traits and carcass price [2], the effect of backfat thickness on the factor of carcass grade and price [12], contribution of yield and quality traits of Hanwoo to auction price [15], and contribution of the carcass trait to the price of Hanwoo steer [16].…”
Section: Introductionmentioning
confidence: 99%